اﻻﻓﻀﻠﯿﺔ ﺑﯿﻦ اﻟﻨﺺ اﻟﻨﺎﺳﺦ واﻟﻤﻨﺴﻮخ (Journal of the College of Education for Women, 2019)
The beholder in the book of God find a tremendous amount of ideas that need to be parking and hopes, including the issue of preference between the Quranic texts that came in verse transcription ,in this research stand on the words opinions of scientists in this differentiation by looking at this text and extrapolate those words The correct statement. Search Quranic texts requires understanding of the text, and understanding requires that the walking path legitimate, not only linguistically path, or another path if be logically Valmsar path language alone does not help to understand Murad Street, Vmradh does not understand words only text understanding, but by and Balqraún legitimacy that had meaning of the text, not all is obligatory, not all forbidden for this prohibition, it may well be the scar Oalabahh, may be forbidden for hatred. has plagued Muslims these days much like those who rush to the analysis and prohibition once reading a command or prohibition in verse or talk. The logical path is not a correct path to understanding legitimate, because it is not the path taken by the Ancestors in understanding, but introduced later, when he entered the logic Muslim lands by Greek philosophy, and adopted by some Muslims a way of understanding. The correct way to discuss the text of a legitimate and understanding or awareness fully aware, they must know three things: The first: to know the words and structures of any knowledge of the Arabic language syntax and morphology and eloquence. Second: Knowing ideas legitimate knowledge of forensic science, such as interpretation and modern jurisprudence. Third: Knowing the reality of the text to be understood. They must know these things, even through knowledge of them just knowledge in order to reach the correct legal opinion on any question.